DNA methylation analysis of AKT1 promoter and HTR2A exon-I of Malaysian schizophrenia multiplex families with lower cognitive performance - Erna Laere,; Chow, Tze Jen; Tang, Pek Yee; Loh, Siew Yim; Yong, Hoi Sen; Abdul Kadir,; Abu Bakar,; Tee, Shiau Foon (Penerbit Universiti Kebangsaan Malaysia, 2020)
Dysfunction of cognitive performance in schizophrenia has been associated with aberrant alteration of DNA methylation of several schizophrenia-risk genes. AKT1 and HTR2A are among the candidate genes for schizophrenia. Their expressions were found reduced in schizophrenia patients. Thus, we aimed to study the methylation status of AKT1 promoter and HTR2A exon-I in Malaysian schizophrenia patients and their affected family members. In this study, each participant was required to perform Trail Making Test (TMT) part A and B to measure their cognitive performance. Genomic DNA extracted from the peripheral blood of 12 Malaysian schizophrenia families and 12 controls families, was subjected to bisulfite conversion. The methylation status of CpG sites of AKT1 promoter at Chr14: 104796054 and HTR2A exon-I at Chr13: 46896918 were identified using methylation-specific polymerase chain reaction (MSP). Our results showed that schizophrenia patients performed worse in both TMT-A and B (p<0.0001) than healthy controls. The patients also displayed significantly (p=0.023) high level of methylation in AKT1 promoter compared to controls. Meanwhile, no significant difference (p=0.248) in methylation status was observed in HTR2A exon-I between schizophrenia and control groups. Therefore, methylation of AKT1 promoter in peripheral bloods of patients may involve in cognitive impairment and schizophrenia pathology. In addition, we were able to demonstrate the heritability of DNA methylation status across family members.